Thirty-Day and 90-Day Episode of Care Spending Following Heart Failure Hospitalization Among Medicare Beneficiaries. Issue 7 (5th July 2022) - Reinhardt, Samuel W.; Clark, Katherine A.A.; Xin, Xin; Parzynski, Craig S.; Riello III, Ralph J.; Sarocco, Phil; Ahmad, Tariq; Desai, Nihar R.
Abstract : BACKGROUND: Despite growing interest in value-based models, utilization patterns and costs for heart failure (HF) admissions are not well understood. We sought to characterize Medicare spending for patients with HF for 30- and 90-day episodes of care (which include an index hospitalization and 30 or 90 days following discharge) and to describe the patterns of post-acute care spending. METHODS: Using Medicare fee-for-service administrative claims data from 2016 to 2018, we performed a retrospective analysis of patients discharged after hospitalization with primary discharge diagnoses of systolic HF, diastolic HF, hypertensive heart disease (HHD) with HF, and HHD with HF and chronic kidney disease. We analyzed coding patterns across these groups over time, median 30- and 90-day payments, and costs allocated to index hospitalization and postacute care. RESULTS: The study included 935 962 patients discharged following hospitalization for HF (systolic HF: 178 603; diastolic HF: 165 156; HHD with HF: 226 929; HHD with HF and chronic kidney disease: 365 274). The proportion of HHD codes increased from 26% of HF hospitalizations in 2016 to 91% in 2018. There was substantial spending on 30-day (median 13 330, interquartile range 9912–22 489) and 90-day episodes (median 21 658, interquartile range 12 423–37 630) for HF with significant variation, such that the third quartile of patients incurred costs 3 times the amount of the first quartile. Across all codes, the index hospitalization accounted for ≈70% of 30-day and 45% of 90-day spending. Sixty-one percent of postacute care spending occurred 31 to 90 days following discharge, with readmissions and observation stays (36%) and skilled nursing facilities (27%) comprising the largest categories. CONCLUSIONS: This patient episode-level analysis of contemporary Medicare beneficiaries is the first to examine 90-day spending, which will become an increasingly important pasyment benchmark with the expansion of the Medicare Bundled Payments for Care Improvement Program. Further investigation into the drivers of costs will be essential to provide high-value HF care.